2019
DOI: 10.1080/17476348.2019.1578212
|View full text |Cite
|
Sign up to set email alerts
|

Pleural infection: a closer look at the etiopathogenesis, microbiology and role of antibiotics

Abstract: BACKGROUND: Pleural infection is a condition that continues to pose a significant challenge to respiratory physicians. We hypothesise that the main barriers to progress include a limited understanding of the pathogenesis, microbiology and role of antibiotics in the pleural space. DATA SOURCE: PubMed was searched for articles related to adult pleural infection using the terms 'pleural infection', 'empyema' and 'parapneumonic'. The search focused on developments in the last ten years, with any older citations on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 94 publications
1
29
0
Order By: Relevance
“…Though an oversimplification, it is proposed that IPFT acts to disrupt the fibrin-rich adhesions via the activation of plasminogen and may have something of a lavage effect by stimulating pleural fluid production, whilst DNase reduces pleural fluid viscosity through the breakdown of extracellular DNA and biofilm formation. It is their synergistic action that results in better drainage and resolution of pleural infection [66,[76][77][78][79][80][81]. These findings build on the earlier work by Tillet and Sherry but also go some way in confirming other proofof-concept studies [61,64,82,83].…”
Section: Intrapleural Enzyme Therapy (Iet)supporting
confidence: 80%
See 1 more Smart Citation
“…Though an oversimplification, it is proposed that IPFT acts to disrupt the fibrin-rich adhesions via the activation of plasminogen and may have something of a lavage effect by stimulating pleural fluid production, whilst DNase reduces pleural fluid viscosity through the breakdown of extracellular DNA and biofilm formation. It is their synergistic action that results in better drainage and resolution of pleural infection [66,[76][77][78][79][80][81]. These findings build on the earlier work by Tillet and Sherry but also go some way in confirming other proofof-concept studies [61,64,82,83].…”
Section: Intrapleural Enzyme Therapy (Iet)supporting
confidence: 80%
“…Intrapleural antibiotic therapy has often been proposed as a way of overcoming the poor pleural penetrance seen with a number of antibiotic classes. A recent review found little evidence to support the routine use of these therapies in post-pneumonic pleural infection, although there is more evidence for its use in post-pneumonectomy infections [80]. A number of antibiotic-eluting drainage catheters are now commercially available, and a recent study was able to demonstrate sustained release of bactericidal concentrations of penicillin within the pleural space compared to an intravenous regime in healthy rabbits [123].…”
Section: Alternative Therapies and Future Directionsmentioning
confidence: 99%
“…Antibiotic choice should be dictated by local prescribing policies and often empirically with adequate aerobic and anaerobic cover unless culture results are available. The role of antibiotics in pleural infection has been recently reviewed [24]. The duration of course and timing of the switch from intravenous to oral has not been evaluated in randomised clinical trials, but generally should be governed by clinical response and experts would advocate a total of 4 weeks of antibiotic therapy.…”
Section: Management Of Pleural Infectionmentioning
confidence: 99%
“…Studies of antibiotic penetration in human pleural fluid are lacking and based on small numbers [43]. As recently reviewed, animal model data would suggest that most antibiotics exceed the minimum inhibitory concentration (MIC) for the bacteria for which it would normally be used [45]. The notable exception is gentamicin and therefore guidelines recommend against the use of aminoglycosides in pleural infection [27].…”
Section: Antibiotics In Pleural Infectionmentioning
confidence: 99%
“…The current recommendation is that the switch from intravenous to oral therapy be guided by cessation of pyrexia, clinical improvement and resolution of inflammatory markers, aiming for a total duration of 4 weeks as a minimum [27]. As recently reviewed, there is currently no role for intrapleural antibiotics in the routine treatment of pleural infection [45].…”
Section: Antibiotics In Pleural Infectionmentioning
confidence: 99%